Pleiotropic effects of DCLK1 in cancer and cancer stem cells - Chhetri, Dibyashree; Vengadassalapathy, Srinivasan; Venkadassalapathy, Santhosh; Balachandran, Varadharaju; Umapathy, Vidhya Rekha; Veeraraghavan, Vishnu Priya; Jayaraman, Selvaraj; Patil, Shankargouda; Iyaswamy, Ashok; Palaniyandi, Kanagaraj; Gnanasampanthapandian, Dhanavathy (Frontiers in Molecular Biosciences, 2022)
Doublecortin-like kinase 1 (DCLK1), a protein molecule, has been identified as a tumor stem cell marker in the cancer cells of gastrointestine, pancreas, and human colon. DCLK1 expression in cancers, such as breast carcinoma, lung carcinoma, hepatic cell carcinoma, tuft cells, and human cholangiocarcinoma, has shown a way to target the DCLK1 gene and downregulate its expression. Several studies have discussed about the inhibition of tumor cell proliferation along with neoplastic cell arrest when the DCLK1 gene, which is expressed in both cancer and normal cells, was targeted successfully. In addition, previous studies have shown that DCLK1 plays a vital role in various cancer metastasis. The correlation of DCLK1 with numerous stem cell receptors, signaling pathways, and genes suggests its direct or an indirect role in promoting tumorigenesis. Moreover, the impact of DCLK1 was found to be related to the functioning of an oncogene. The downregulation of DCLK1 expression by using targeted strategies, such as embracing the use of siRNA, miRNA, CRISPR/Cas9 technology, nanomolecules, specific monoclonal antibodies, and silencing the pathways regulated by DCLK1, has shown promising results in both in vitro and in vivo studies on gastrointestinal (GI) cancers. In this review, we will discuss about the present understanding of DCLK1 and its role in the progression of GI cancer and metastasis.